Validation of the Dépistage Cognitif de Québec: A New Cognitive Screening Tool for Atypical Dementias. (25th May 2017) - Laforce, Robert; Sellami, Leila; Bergeron, David; Paradis, Audrey; Verret, Louis; Fortin, Marie-Pierre; Houde, Michèle; Roy, Martin; Poulin, Stéphane; Macoir, Joël; Hudon, Carol; Bouchard, Rémi W
Abstract: Objective: This study aimed to validate and provide normative data for the Dépistage Cognitif de Québec (DCQ; www.dcqtest.org ), a new cognitive screening tool for atypical dementias. Method: The DCQ was developed by expert behavioral neurologists and clinical neuropsychologists based on updated criteria for Alzheimer's disease, primary progressive aphasia, and behavioral variant frontotemporal dementia. It targets five relevant domains: Memory, Visuospatial, Executive, Language, and Behavior. Validation was performed in a population-based sample of 410 healthy French-speaking Canadians aged between 50 and 89 years old. Normative data were derived from a subsample of 285 participants. Results: Mean DCQ total score (out of 100) was 89.17 ( SD = 7.36). Pearson's correlation coefficient showed a strong and significant correlation ( r = .71, p < .001) with the Montreal Cognitive Assessment. Internal consistency for the cognitive domains assessed by Cronbach's alpha was satisfactory (.74). Test–retest reliability was adequate (Pearson's coefficient = . 70, p < .001) and interrater reliability, excellent (intraclass correlation = .99, p < .001). Normative data shown in percentiles were stratified by age and education. Conclusions: This study suggests that the DCQ is a valid and reliable cognitive screening test. Application of the DCQ on populations with atypical dementias is underway to derive sensitivity and specificity values for various dementias.